2019
DOI: 10.1111/bjhp.12377
|View full text |Cite
|
Sign up to set email alerts
|

What are mass media interventions made of? Exploring the active content of interventions designed to increase HIV testing in gay men within a systematic review

Abstract: Purpose Mass media HIV testing interventions are effective in increasing testing, but there has been no examination of their theory or behaviour change technique (BCT) content. Within a heterogeneous body of studies with weak evaluative designs and differing outcomes, we attempted to gain useful knowledge to shape future interventions. Methods Within a systematic review, following repeated requests to the authors of included studies for intervention materials, the Theory Coding Scheme, the Theoretical Domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness (McDaid et al, 2019), the active content of interventions (Flowers et al, 2019) and affect used within interventions (Langdridge et al, 2020) can be found elsewhere. The current analyses employed rigorous data extraction tools to attempt to identify the common social marketing principles and visual design elements associated with effectiveness across a range of HIV testing campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness (McDaid et al, 2019), the active content of interventions (Flowers et al, 2019) and affect used within interventions (Langdridge et al, 2020) can be found elsewhere. The current analyses employed rigorous data extraction tools to attempt to identify the common social marketing principles and visual design elements associated with effectiveness across a range of HIV testing campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness ( McDaid et al, 2019 ), the active content of interventions ( Flowers et al, 2019 ) and affect used within interventions ( Langdridge et al, 2020 ) can be found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that trust in sources is an essential component associated with both individual understanding of information and willingness to act on it [ 12 ]. Additionally, research in China has shown that people vary in their risk perception of COVID-19 depending on whether they received information from mass media or social media [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The broader systematic review from which the data for this study have been garnered has sought to utilize a pluralistic approach to better understand intervention content and its relationship to effectiveness. To date, we have examined effectiveness per se (McDaid et al , 2019), behaviour change techniques and theoretical domains (Flowers et al , 2016), and the social marketing, mode of delivery, and use of imagery focusing upon the social position of the viewer and context of viewing (Riddell et al , under review). In contrast to these analyses, the focus in the present study is on an analysis of the cultural determinants of visual materials, as visual materials provide one of the primary means for the encoding of affect within mass media oriented health communications (Langdridge, Davis, et al , 2019; Noar, Francis, et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%